Applying Benjamin Bloom’s Taxonomy Ideas in Adult Learning - Grebin, Nataliia; Grabovska , Sofia; Karkovska, Ruslana; Vovk, Anna (Journal of Education Culture and Society, 2020)
Aim. The research goal of this paper is to theoretically substantiate the feasibility of using Benjamin Bloom’s psychological and pedagogical model and its modifications in the adult learning system. Methods. The study used the methods of theoretical analysis, synthesis and modelling of the implementation options for Bloom’s techniques in the training of adults. Results and Conclusions. The analysis showed that the use of techniques based on Bloom’s taxonomy, modified for adult training, makes it possible to develop students’ skills and abilities to thoroughly and comprehensively analyse the problem, and to find creative, effective solutions. Such a sequence of task setting as “reproduction” (knowledge), “understanding” (comprehension), “application,” “analysis,” “evaluation,” and “creation” is proposed as a general scheme of various training for adults. In particular, an example of the design of training in developing communication skills and training in overcoming procrastination skills is given.